EFFECT OF ADMINISTRATION OF RED GINGER AND GARLIC EXTRACT ON CHANGES IN IMMUNOGLOBULIN G (IG-G) IN CHILDREN AGED 8 YEARS SUFFERING FROM BRONCHIAL ASTHMA IN THE WORKING AREA OF THE TANJUNGPINANG CITY HEALTH CENTER - Suharti Suharti; Muji Hartinah; Artia Diarina (Bajang Institute, 2023)
The bioactive components in red ginger consist of gingerols, shogaols, and zingerons which are a group of phenolic compounds. The oleoresin ginger bath ranged from 3.2-9.5%, while the content of gingerol in oleoresin was between 14-25% and shogaol in oleoresin was between 2.8-7.0%, which were investigated for their anti-inflammatory, antioxidant, antibacterial and anti-platelet properties.. Garlic also contains essential oil components, which have antibacterial activity that works by inhibiting the formation of bacterial cell membranes. The research design was a cohort analytic observational study with a prospective design. Sampling was carried out by purposive sampling method and obtained 34 child respondents with a history of or currently experiencing asthma, with 24 boys and 10 girls. This research was conducted in the Work Area of ​​the Tanjungpinang City Health Center and was approved by the Research Ethics Commission of the Jakarta I Ministry of Health Polytechnic with Number 130/KEPK/VIII/2018. Data were analyzed using Chi Square. The results showed that there was a change in IgG control values ​​in this case seen from changes in oxygen saturation in the blood of 4.06 g, namely before (91.38%) and after (95.44%) in children with beta-agonist effects that work with smooth muscle relaxation (ASM).